Para uma (bio)ética da finitude. Leituras sobre a subjetividade das ideias de corpo e de saúde no pensamento gadameriano - Azevedo, Stella Zita de (Trabalhos de Antropologia e Etnologia, 2020)
Starting from the modern oblivion of existential-phenomenological qualities of finitude and fragility of the patient in his state of dependence, we enfocus that, by the narrative act (subjective dimension of narrative) the patient/ ill person feels what he experiences as a ‘gap’ in his personal history. Allowing the exploration of the specificity of the disposal of narrative themes within a given existence, the narrative resends us to the universally shareable experiences in terms of formal and generative structure (e.g. hope, anguish, pain, desire). These are the narrative themes of the suffering and/or dying subject, which give flesh to common principles for specific caregiving in a social group, facilitating the acting together within the framework of an applied ethics, which respects the singularity of the person. A methodology of narration should, therefore, be based on the constitution of an ethics of significance, action and decision on the collective plan, privileged place for reflection, where the emotions and the consequences of the action are reflected and where the applied ethics (applicatio) is manifested as normalizing rewriting activity. The diffusion of the narrative ethics culture is, therefore, one of the foundations of the (re) construction of a form of social bonding capable of not letting us wander between individualism and communitarianism, whilst its work reside in the articulation between the narrative dimension of the case (subjective historicity) and the demand for guiding principles of judgment (historicity in clinic field), preserving from arbitrary of the political-economic and the medical decisions.